Design of external shading devices in Mansehra, Pakistan and their role in climate change - Iqbal, Asifa; Nazir, Humaira; Awan, Muhammad Ashar (Frontiers in Energy Efficiency, 2023)
With the rising global temperatures, developing countries are one of the most adversely affected countries by climate change. Furthermore, changes in lifestyle and unsustainable ways of development have resulted in a shift away from passive strategies in the construction industry, which contribute to excessive energy consumption. This demands immediate action to use passive strategies and one of the most widely used passive strategies is shading devices, which can significantly lower the indoor temperature and give the structure the most efficient energy performance. Shading devices were a dominant identity of traditional architecture in Pakistan; however, it has been evident during the past decade the use of such devices has become obsolete due to modernized solutions. This study aims to examine the performance and effectiveness of shading devices in terms of heat gain and daylight levels in residential areas. A comparative case study methodology has been used. The fixed overhanging shading devices of six residential units in Mansehra City, Khyber Pakhtunkhwa province, Pakistan, have been used. Sun angles are calculated through the SketchUp tool Curic Sun to analyze and determine the performance of overhanging in both summers and winters. This article reveals south shading devices as an essential part of houses built before 2000 in Mansehra City. Though, houses built after 2000 do not consider using south shading devices to maximize energy use. This study emphasizes considering the type, design, and use of shading devices according to the building's orientation to improve building performance and energy efficiency.